Pengaruh Penggunaan Paylater dan Cash On Delivery terhadap Perilaku Impulse Buying Pengguna E-Commerce Shopee di Kota Kupang - Bangngu, Sarah G.; Fanggidae, Rolland E.; Kurniawaty, Merlyn; Fanggidae, Ronald P.C. (Jurnal Bisnis dan Pemasaran Digital, 2023)
Purpose: This study aims to determine the effect of using Paylater and Cash on the Impulse Buying behavior of e-commerce shopee users in Kupang City. The population in this study is the people of Kupang city who use Paylater and Cash on delivery e-commerce shopee, the data used in this study were obtained through a questionnaire. Method: The data analysis technique in this study used descriptive analysis, instrument test, classical assumption test, multiple regression analysis, and hypothesis testing using SPSS version 26. The method used in this study is quantitative. Result: The results of this study show that the paylater variable has a partially significant effect on the impulse buying behavior of e-commerce shop users in the city of Kupang. Limitation: Determining the sample using the Slovin method resulted from the calculations of 100 residents of Kupang City. Contribution: The cash on delivery variable has a significant effect on the impulse buying behavior of Shopee e-commerce users in the city of Kupang. Simultaneously, paylater and cash on delivery have a significant effect on the impulse buying behavior of e-commerce shop users in the city of Kupang.